New information about the seismicity of the Russian Arctic based on the work of the seismic station “Severnaya Zemlya” - G. N. Antonovskaya; S. M. Kovalev; Ya. V. Konechnaya; V. N. Smirnov; A. V. Danilov; Г. Н. Антоновская; С. М. Ковалев; Я. В. Конечная; В. Н. Смирнов; А. В. Данилов (Arctic and Antarctic Research, 2018)
In November 2016 a seismic station “Severnaya Zemlya“ with code SVZ was installed on the Severnaya Zemlya archipelago (Bolshevik island, research facility “Ice base “Baranov’s cape”) by joint efforts N. Laverov Federal Center for Integrated Arctic Research (Arkhangelsk) and Arctic and Antarctic Research Institute (St. Petersburg). This station was included in the Arkhangelsk seismic network and a broadband set of CMG-6TD devices (Great Britain) was installed there.The microseismic background is characterized by a low level of industrial noise which allows to obtain the high-quality seismic information. Over 400 regional earthquakes and 25 local seismic events were recorded by seismic station SVZ within period from November 2016 to December 2017. Processing of regional earthquakes was carried out by us according to the data of at least three stations. We used wave forms from the Arctic stations of the Arkhangelsk seismic network and/or other seismological networks, whose stations are installed in the Arctic. In general, the majority of seismic events occur at epicentral distances of 3.5°–4° (i.e., they are regional) and associated with Gakkel Ridge. The strongest earthquakes are recorded from the areas of the Knipovich Ridge and Spitsbergen. Regional earthquakes magnitude range recorded by the SVZ is from 3.1 to 5.4. ML = 2.5 — it is the value of the magnitude from which the station registers earthquakes in full range. Local earthquakes magnitude range is from 1.2 to 4.9. Weak earthquakes with МL < 2.5 predominate.The difficulty is that out of the total number of regional and local events registered by SVZ only part of them could be processed according to the standard seismic rule (at least 3 stations). These events were included in the Seismic Catalogue. The predominant numbers of earthquakes are recorded only by SVZ station and they can not be included in the Seismic Catalogue due to the low quality data processing seeing that only one station was used. However, even in the first approximation these ...